Upaya Memaksimalkan Kemampuan Lompat Jauh dengan Meningkatkan Performa Pada Siswa Kelas X MIPA 4 SMA Negeri 2 Siak Hulu - Yayuk Sri Andayani (Departement of Mathematics Education, 2020)
The purpose of this study was to maximize long jump abilities by improving performance in Class X students of SMAN 2 Siak Hulu in the 2019/2020 school year. This study used two rounds of action research. Each round consists of two meetings, with stages of design, activity and observation. Reflection and revision. The target of this research is Class X students from the data obtained in the form of practical test results, observation sheets for teaching and learning activities. 81%) and cycle III (91%). The conclusion of this study is that the method of improving performance can have a positive effect on the learning motivation of Class X Mathematics and Natural Sciences 4 students and the learning model can be used as an alternative physical education.